Development of E-Module Based on Problem Based Learning on Human Reproductive System Material for Class XI SMA - Anwar, Sitti Aisyah; Sulisetijono, Sulisetijono; Sari, Murni Sapta (BIOEDUKASI, 2024)
The existence of biology teaching materials on human reproductive system material in the form of PBL-based e-modules makes learning more interesting. The purpose of this study was to determine the validity and practicality of the PBL-based human reproductive system e-module. This type of research is development using the Lee and Owens model. The results of validation of material experts 100% and field practitioners 97.50%, media experts and teaching materials 98.34% with a very valid category. The results of the practicality test from the lecturer were 97%, the one to one trial was 86.58%, the small group trial was 87.42% and the field test practicality value was 87.44% which was included in the very practical category. Based on the results of this study, it can be concluded that the PBL-based human reproductive system e-module is very valid and practical.